2017
DOI: 10.18203/2394-6040.ijcmph20170765
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent friendly health services: where are we actually standing?

Abstract: Background: Services for adolescents are highly fragmented, poorly coordinated and uneven in quality. Adolescent-friendly services (AFHS) should be able to attract young people, meet their needs comfortably and with sensitivity, and retain young clients for continuing care. With this background, the present study was carried out to study the implementation status of Adolescent friendly health services and to determine compliance with quality standards.Methods: Present cross sectional study was carried out at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 1 publication
2
24
0
Order By: Relevance
“…11 Understandably, the trained providers who knew about GATHER approach listened attentively to the client as compared to where the services were delivered by clinical providers, which makes a case for improving and expanding the scope of training and placement of trained providers in all health care facilities. Similar findings have been reported by Wadhwa R et al 17 and Bhat et al 9 Contrary to the findings of the present study Dixit GT et al, reported that more than 70% provided health education, counseling and information about services and they provided services without discrimination, 10 which provides a silver lining.…”
Section: Discussionsupporting
confidence: 86%
“…11 Understandably, the trained providers who knew about GATHER approach listened attentively to the client as compared to where the services were delivered by clinical providers, which makes a case for improving and expanding the scope of training and placement of trained providers in all health care facilities. Similar findings have been reported by Wadhwa R et al 17 and Bhat et al 9 Contrary to the findings of the present study Dixit GT et al, reported that more than 70% provided health education, counseling and information about services and they provided services without discrimination, 10 which provides a silver lining.…”
Section: Discussionsupporting
confidence: 86%
“…The same problem also occurred in Other Low Middle Income Countries (LMIC), including India. In India, only a small proportion of adolescents could access the AFHS, and they were mostly girls (Dixit et al, 2017). Meanwhile, Kenya and Ethiopia had the higher proportion of adolescents' access which was 38.5% and 36%, respectively (Motuma et al, 2016;Luvai et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Research on the quality assessment of AFHS in Southern Africa showed that there were no health facilities that met the minimum friendly adolescent health facility standards in two provinces studied (James et al, 2018). Another study on adolescents' access to AFHS in India showed that the program was limited to only a small proportion of female adolescents (Dixit et al, 2017). Meanwhile, studies in sub-country areas in Kenya and Ethiopia found only 38.5% and 36% of adolescents had respectively utilized AFHS even though improvements in adolescents' access to the program have been made, such as training peer educators from schools and organizing school-based reproductive health education programs (Motuma et al, 2016;Luvai et al, 2017).…”
Section: Original Researchmentioning
confidence: 99%
“…Services pertaining to resolving queries about physiological changes during adolescence, menstruation-and nutrition-related issues, reproductive tract infections, and skin disorders were sought by adolescents [11][12][13]26]. Quite often, privacy and confidentiality are maintained in clinics, [13,28] but it is still breached in many places [26]. However, providers lacked comprehensive knowledge about the management of adolescent health problems, and their adherence to protocols or guidelines was lacking [13].…”
Section: Discussionmentioning
confidence: 99%
“…Health workers, especially the frontline workers and medical officers, have been trained in delivering adolescent-friendly health services [11]. However, studies suggest a huge gap between the awareness and utilization of adolescent health services in the communities [12,13].…”
Section: Introductionmentioning
confidence: 99%